A comparative study on the marginal integrity of two commercially available brands of calcium hydroxide liners in vitro - Oviedo, Marlene Imelda V.
Autoradiographic procedures revealed that Life is more marginally stable than Dycal after acid-etching. This due to a resin present in Life and not found in Dycal which forms a chelation reaction between the base paste and catalyst in Life, thus results in a set material which makes the product resistant to the acid etchant during a 60 sec. application.